Review of the treatment of psoriatic arthritis with biological agents: choice of drug for initial therapy and switch therapy for non-responders - D’Angelo, Salvatore (Open Access Rheumatol, 2017)
Psoriatic arthritis (PsA) is a heterogeneous chronic inflammatory disease with a broad clinical spectrum and variable course. It can involve musculoskeletal structures as well as skin, nails, eyes, and gut. The management of PsA has changed tremendously in the last decade, thanks to an earlier diagnosis, an advancement in pharmacological therapies, and a wider application of a multidisciplinary approach. The commercialization of tumor necrosis factor inhibitors (adalimumab, certolizumab pegol, etanercept, golimumab, and infliximab) as well as interleukin (IL)-12/23 (ustekinumab) and IL-17 (secukinumab) inhibitors is representative of a revolution in the treatment of PsA. No evidence-based strategies are currently available for guiding the rheumatologist to prescribe biological drugs. Several international and national recommendation sets are currently available with the aim to help rheumatologists in everyday clinical practice management of PsA patients treated with biological therapy. Since no specific biological agent has been demonstrated to be more effective than others, the drug choice should be made according to the available safety data, the presence of extra-articular manifestations, the patient’s preferences (e.g., administration route), and the drug price. However, future studies directly comparing different biological drugs and assessing the efficacy of treatment strategies specific for PsA are urgently needed.